2012
DOI: 10.1097/nrl.0b013e318272f7ef
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Daytime Activity and Altered Sleep-Wake Patterns May Predict Transition to Mild Cognitive Impairment or Dementia

Abstract: Disrupted circadian rhythm measures, including lower amplitude, a less robust rhythm, and delayed timing of peak activity on wrist actigraphy, were predictive of future development of MCI or dementia in cognitively normal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 12 publications
4
35
0
2
Order By: Relevance
“…In this sense, Cochrane et al (2012) [25] observed a phase delay in this rhythm in MCI subjects. Furthermore, other studies have identified this phase delay of the rest-activity rhythm as a predictor for developing MCI [9, 10]. However, a recent study combining polysomnography, actigraphy, and melatonin analysis showed a clear phase advance in sleep and dim light melatonin onset in patients with MCI [11], similar to that observed by us using rhythmic multivariable recordings.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this sense, Cochrane et al (2012) [25] observed a phase delay in this rhythm in MCI subjects. Furthermore, other studies have identified this phase delay of the rest-activity rhythm as a predictor for developing MCI [9, 10]. However, a recent study combining polysomnography, actigraphy, and melatonin analysis showed a clear phase advance in sleep and dim light melatonin onset in patients with MCI [11], similar to that observed by us using rhythmic multivariable recordings.…”
Section: Discussionsupporting
confidence: 74%
“…This circadian alteration is similar to that observed during normal aging, since elderly people consistently show a phase advance in their circadian rhythms [2]. This discrepancy between our study and the results of Cochrane (2012) [25], Schlosser Covell et al (2012) [10], and Tranah (2011) [9] could be possibly attributed to how phases are calculated. These authors calculate the acrophase of the rest-activity rhythm using the cosinor method.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Recent clinical studies have found that age-related declines in circadian function can lead to mild cognitive impairment or dementia (2, 3). These memory deficits are not simply a consequence of poorer sleep, because reductions in circadian rhythm amplitude and robustness can accelerate progression of mild cognitive impairment or dementia even when sleep quality is maintained (2, 3). The observation that circadian timing is substantially weakened among people with Alzheimer's disease has raised the possibility that cognitive deficits might be treated by improving circadian function (46).…”
mentioning
confidence: 99%
“…However, recent research suggests circadian dysfunction contributes to and escalates neurodegenerative pathologies (Musiek 2015). In clinical studies, dampened or shifted circadian rhythms in aging individuals were predictive of increased risk of mild cognitive impairments and dementia (Tranah et al 2011;Schlosser Covell et al 2012). Similarly, weaker circadian rhythms were also predictive of future cognitive impairments in older individuals without dementia (Walsh et al 2014).…”
Section: The Circadian Clock Aging and Neurodegenerative Diseasesmentioning
confidence: 99%